Fire ants: What do rural and urban areas show us about occurrence, diversity, and ancestral state reconstruction? - Ramalho, Manuela de O.; Menino, Leonardo; Souza, Rodrigo F.; Kayano, Debora Y.; Alves, Juliana M. C.; Harakava, Ricardo; Nagatani, Victor H.; Silva, Otavio G. M.; Bueno, Odair C. [UNESP]; Morini, Maria S. C. (Soc Brasil Genetica, 2022)
In South America, Solenopsis saevissima and S. invicta are the most common fire ants. Nests are founded in areas under anthropic interference like urban or rural areas, but S. invicta is found preferentially in those with the greatest anthropic interference. However, we do not know the rates at which they exist in anthropized areas next to high density of native vegetation. Areas with 60 to 90% of native Atlantic Forest were selected to verify the occurrence of both species in rural and urban areas. We investigated the molecular diversity and applied the reconstruction of the ancestral state analysis for each species. A total of 186 nests were analyzed and we found that the two species had the same proportion in the urban area. However, S. saevissima had a higher rate of prevalence in the rural area, in addition to having a greater number of haplotypes and ancestry associated with this type of habitat for the region. S. invicta had the same number of haplotypes in both rural and urban regions, and less haplotypic diversity. We conclude that S. saevissima is a species typically associated with rural areas and S. invicta, although present, is not dominant in urban areas.
Keywords: Biodiversity; haplotype diversity; DNA barcoding; mtDNA